2021
DOI: 10.1002/ecy.3534
|View full text |Cite
|
Sign up to set email alerts
|

Predator complementarity dampens variability of phytoplankton biomass in a diversity‐stability trophic cascade

Abstract: Trophic cascadesindirect effects of predators that propagate down through food webshave been extensively documented in many ecosystem types. It has also been shown that predator diversity can mediate these trophic cascades and, separately, that herbivore biomass can influence the stability of primary producers. However, whether predator diversity can cause cascading effects on the stability of lower trophic levels has not yet been studied. We conducted a laboratory microcosm experiment and a field mesocosm exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Based on previous research, we expected Neoplea to have differential effects on zooplankton based on behavior and size ( Rakowski et al, 2021 ). Copepods have faster escape responses than the other zooplankton present, so we analyzed their biomass separately.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous research, we expected Neoplea to have differential effects on zooplankton based on behavior and size ( Rakowski et al, 2021 ). Copepods have faster escape responses than the other zooplankton present, so we analyzed their biomass separately.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, interspecific competition for scarce resources (e.g., space) can increase with diversity (Menge & Sutherland, 1987), particularly in temperate marine systems composed of generalist species (Pellissier, 2015). However, there is little information about the relative influence of interactions between predators and prey and interactions among competitors on community stability in natural systems (Ives et al., 2005; Rakowski et al., 2021) because it is difficult to extend investigations past one trophic level of competing taxa (Loreau et al., 2021). When asynchrony and stability have been assessed in multitrophic communities, systems may be more stable when the multitrophic linkages rather than just the competitive linkages are considered (Downing et al., 2014; Firkowski et al., 2022; Xu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…number of trophic levels) diversity (Albert et al, 2022;Buzhdygan et al, 2020;Duffy et al, 2007;Soliveres et al, 2016;Thébault & Loreau, 2003;Wang & Brose, 2018). While these studies reported generally positive biodiversity-ecosystem productivity relationships, their strengths vary considerably across trophic levels and ecosystems (Cardinale et al, 2006;Gruner et al, 2008;Katano et al, 2015;Maureaud et al, 2020;Rakowski et al, 2021;Schneider et al, 2016). One possible explanation for the variable biodiversityproductivity relationships in food webs is the structural complexity of multitrophic systems, as the topology and strengths of trophic interactions act together with species diversity in regulating ecosystem productivity (Ives et al, 2005;Maureaud et al, 2020;Thébault & Loreau, 2003;Wang et al, 2019;Wu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has indicated that food web connectance and interaction strength play important roles in regulating ecosystem primary productivity (Finke & Denno, 2005;Poisot et al, 2013;Thébault & Loreau, 2003;Wang et al, 2019). One key mechanism underlying the biodiversity effect on primary productivity in food webs is trophic complementarity, which characterizes niche differentiations between species in both resource use and natural enemies (Albert et al, 2022;Poisot et al, 2013;Rakowski et al, 2021). The effect of trophic complementarity was predicted to decrease with increasing connectance between trophic levels (Poisot et al, 2013); therefore, ecosystem productivity may be lower in more connected communities.…”
Section: Introductionmentioning
confidence: 99%